Objective on line assessment of the performance of flux cored wires by real time computer based monitoring - Chawla, Kawalprit Singh (Cranfield University, 1993)
The aim of this research was to devise an innovative technique to obtain an objective assessment of the quality performance of tubular cored wires by sensing and measuring the signals available during welding. The work comprised: Identification of the parameters to assess. A study of the different monitoring techniques. Design of specific quality evaluation methods. The production of a system which allowed a quality index of welding performance to be obtained. Initially, the arc voltage, arc current, wire feed rate, arc light and arc sound signals were identified as possible sources of useful information. After a useful technique was accepted, the non-useful techniques were abandoned and a quality measuring instrument was built. The work involved development of statistical analysis techniques, Fast Fourier Transforms and mathematical modelling. A new approach to process modelling was devised which provided an objective and very flexible method of assessing, comparing and developing welding consumables. The final system was evaluated against conventional subjective assessment techniques and very good correlation was obtained.